Entrepreneurial competency needs of UPLB agribusiness students and directions toward the formulation of a strategy in response to their needs - Divinagracia, Louie A. (Animo Repository, 1993)
The B.S. Agribusiness (BSAB) Program of the University of the Philippines at Los Banos (UPLB) was launched with the endview of producing trained manpower who can pursue and manage their own agribusiness enterprises in the countryside.The private business sector and the academe, however, had observed that most of the UPLB's agribusiness graduates are not being recognized for their entrepreneurship activities. School administrators have expressed their concern regarding the possible low levels of entrepreneurial competencies which agribusiness students possess after graduating from college.The study was conducted to primarily determine the entrepreneurial competency needs of UPLB's agribusiness students, and thereafter recommend directions toward the formulation of a strategy in response to the students' needs.There were eleven entrepreneurial competencies which the study utilized. These competencies may be grouped into three categories, namely: opportunity seeking and resource mobilization competencies knowledge-based competencies and enterprise management competencies.Multidimensional scaling and other multivariate analytical techniques were utilized to generate a spatial representation of UPLB's agribusiness students and alternative BSAB Program designs in multidimensional space. The dimensions represented a set of relevant entrepreneurial competencies. The respondents of the study are the entire 1993 BSAB graduating class. A limited number of alumni operating in areas adjacent to the University were also selected as respondents for control purposes.The study showed that barely 10 percent of the graduating class are certain of pursuing self-employment activities on a full-time basis after graduation. This represented a group of student-respondents who have had the experience of organizing their own businesses while studying, and who were at the same time active in contributing decisions to the businesses of their families.The entrepreneurial competency which had the highest perceived need-level score was having the capability of conducting a systematic analysis in assessing the viability of a proposed business venture. It was also observed that there were large gaps in the levels of competencies which the students need compared to those levels which they possessed. The gaps were higher for those student groups who have had no experience in organizing their own business while in college as well as those who came from families which are not engaged in self-employment activities.Similarly, the findings of the study showed that the current BSAB Program was not providing an adequate level of entrepreneurial competencies needed by the students.